Pengembangan Prototype Model Pembelajaran Pengelolaan Bisnis Start Up Untuk Meningkatkan Kreativitas Mahasiswa - Dede Rusmana (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
The Startup Business Management course is one of the courses taught in the Commerce Education study program, State University of Malang, which is included in the Specialization and Self-Development Courses (SSDC) group and is a transdisciplinary subject. This course allows students of all majors to follow the learning process. It is important to develop a learning model that can accommodate the characteristics of this course. This research is a development research. The resulting product is a learning model syntax prototype in the Start Up Business Management course. The development design that will be used in this study is the ADDIE development design. The ADDIE model stands for Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation. The development results show that the START-UP model has been successfully developed with its own originality and is considered valid by the validator. The conclusion of this research is that the research results can be used in the next process, namely empirical testing and implementation in learning.